An introduction to family medicine - Abril-Collado, Ramiro Orlando (2013)
Family Medicine is the medical specialty effector Primary Care; provides care to the patient and her family in community context. His story has a basis in the tradition of family doctor and has a history of over 40 years of existence in the world, in Peru began in 1989. The practice of family medicine requires a paradigm shift in biomedical to biopsychosocial and support pillars as comprehensiveness, continuity, coordination of care and family counseling. Today this is specialty as primary health care are more necessary than ever.